Studi Komparatif Terkait Kompetensi Guru di Negara Finlandia dan Indonesia - Septy Widyorini; Vika widiana Lestari; Taufik Muhtarom (Journal Innovation In Education, 2024)
: Etymologically, comparative education means comparing two or more educational systems and studying procedures or procedures. It is not surprising that the term "comparative education" is often combined with "comparative education", because both words have the same meaning. In comparative studies we can compare various problems related to teaching strategies, facilities and infrastructure, curriculum and the academic results of students. Therefore, this article aims to discuss in more depth comparative studies regarding the quality of education in Indonesia and Finland. The research method used in writing this article is a qualitative method with data collection and analysis techniques carried out by searching for literature studies through several books and scientific articles as well as other trusted sources. In conclusion, the comparative study between the Indonesian and Finnish education systems shows the importance of educational policies and systems that support the overall development of teacher competency to improve the quality of education. There are several main differences between teacher assessment systems, namely teacher qualifications, assessment methods and educational focus.